Assessment of orthodontic treatment needs using a modified aesthetic scale - Sharihan Khasim; Asma Alhusna Abang Abdullah; Nurul Asyikin Yahya; Rohaya Megat Abdul Wahab (Universiti Kebangsaan Malaysia, 2013)
Early treatment of orthodontic problems is important to ensure the best outcome and to avoid social stigmatization. Treatment is often prioritized based on scales such as the Index of Orthodontic Treatment Need (IOTN). Unfortunately, the conventional aesthetic component of IOTN measurement is slanted towards Caucasian malocclusions. Thus, Asian children find it particularly difficult to rate their appearance on this scale and therefore treatment may be wrongly prioritized. This study aimed to assess the use of a newly modified aesthetic scale in assessing orthodontic treatment need in adolescent. A total of 522 16-year old children were recruited. The subjects as well as the examiner rated the subject’s own dentition according to the conventional scale of aesthetic component of IOTN and the newly modified aesthetic scale. Questionnaire was given to assess the practicality of the two scales. When conventional scale was used, subjects and examiner tends to rate more to the no/slight treatment need category. However, when the newly modified scale was applied, the rating has skewed to the moderate/great need treatment category in both subjects and examiner. Moderate inter-agreement between examiner and subjects were detected when using the modified scale while poor agreement was found when using the conventional scale. Moreover, subjects found the modified scale to be easier and faster to use and more relevant to their own dentition. In conclusion, the newly modified aesthetic scale can be suggested as a better tool in assessing level of orthodontic treatment need in adolescent.